miR‐207 Suppresses the Progression of SiO2‐Induced Pulmonary Fibrosis by Targeting Smad3 to Regulate the TGF‐β1/Smad3 Signaling Pathway in C57BL/6 Mice - Zhao, Jia‐hui; Li, Shuang; Du, Shu‐ling; Han, Gui‐zhi; Li, Huan; Shao, Bo; Liu, Xia; Zhou, Yuting; Zhang, Zhao‐qiang (Journal of biochemical and molecular toxicology, 2025)
ABSTRACT Silicosis is a worldwide occupational disease characterized by irreversible pulmonary fibrosis. Recent studies have showed that microRNAs (miRNAs) may play a crucial role in silicosis progression by modulating fibrosis‐related gene express. In this study, we selected miR‐207 as our research subject because we found that miR‐207 can be match with Smad3 using bioinformatic techniques, which might silence the key fibrosis‐related TGF‐β1/Smad3 signal pathway. In this study, the mice were given silica suspension (20 µg/µL, 80 µL) via nostril once a day for 16 days to establish silicosis models, and then were transfected with miR‐207 mimic or inhibitor. The mice which were given phosphate‐buffered saline (PBS) (80 µL) via nostril were used as control. All mice were killed on Day 45 after the first exposure to dust, after which their lungs were removed for pathological observation and to measure the hydroxyproline content. Then, real‐time polymerase chain reaction and Western blot analysis were applied to detect the relative expression levels of TGF‐β1/Smad3 signaling pathway indicators (TGF‐β1, TGF‐βR, and Smad3), and myofibroblast transformation indicators (α‐SMA and Fn). Results showed that the lung pathological images of silicosis model group mice showed significant fibrosis, and TGF‐β1, TGF‐βR, Smad3, α‐SMA, and Fn were all highly upregulated compared with the control group mice. Intervention with miR‐207 mimics significantly inhibited pulmonary fibrosis in silicosis mice by downregulation of TGF‐β1/Smad3 and inhibiting of myofibroblast formation. Whereas these phenomena were not observed in silicosis mice treated with miR‐207 inhibitor. The results demonstrated that miR‐207 can block the progression of SiO2‐induced pulmonary fibrosis by targeting the TGF‐β/Smad3 signaling pathway. After macrophages are exposed to SiO2, they release inflammatory factors such as TGF‐β, which interact with TGF‐β receptors on fibroblasts, inducing the transdifferentiation of fibroblasts. The inhibition of fibrosis by miR‐207 is achieved by targeting Smad3 in fibroblasts, thereby hindering the progression of silicosis fibrosis.